Pengaruh Stres Kerja dan Disiplin Kerja terhadap Kinerja Pegawai Fakultas Peternakan Universitas Hasanuddin - Muhammad Feryansya; Azhary Ismail; Rahmi Usman (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
The Influence Of Work Stress And Work Discipline On Employee Performance At The Faculty Of Animal Husbandry, Hasanuddin University. Study Of Human Resource Management Program Stim-Lpi Makassar. Supervised By Supervisors Azhary Ismail And Rahmi Usman. This Study Aims To Analyze The Effect Of Work Stress And Work Discipline On Employee Performance At The Faculty Of Animal Husbandry, Hasanuddin University. The Number Of Respondents In This Study Was 38 People, With The Implementation Of The Study Taking Place FromNovember 9, 2024 Until Completion. The Approaches Used Include Quantitative And Qualitative Approaches, With Data Analysis Techniques In The Form Of Multiple Linear Regression. The Results Of The Study Indicate That There Is A Significant Influence Between Work Discipline And Employee Performance At The Faculty Of Animal Husbandry, Hasanuddin University. The Results Show That T Count Is 2.010, T Table Is 2.898, And The Significant Number Is 0.050 ≤ 0.05, Which Indicates That H0 Is Rejected And Ha Is Accepted.